2007
DOI: 10.1080/10934520601015255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cadmium and tributyltin on development and reproduction of the non-biting midgeChironomus riparius(Diptera)—baseline experiments for future multi-generation studies

Abstract: In this study the effects of tributyltin (TBT) and cadmium (Cd) were tested on the freshwater arthropod Chironomus riparius (Diptera) in life-cycle experiments. To this end, the OECD guideline 218 was extended with reproduction relevant parameters (e.g. number of fertile egg masses per female). Based on these reproduction data the number of larvae for next generation and the population growth rate were calculated. Experiments were performed using environmentally relevant concentrations of the test substances i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 19 publications
3
39
1
Order By: Relevance
“…We additionally conducted life-cycle tests with a nominal Cd-concentration of 1.2 mg Cd/kg sediment dw over three subsequent generations. Cd was selected because several studies already indicated the toxicity for chironomid larvae at the chosen concentration range (Watts and Pascoe 2000;Milani et al 2003;Vogt et al 2007a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We additionally conducted life-cycle tests with a nominal Cd-concentration of 1.2 mg Cd/kg sediment dw over three subsequent generations. Cd was selected because several studies already indicated the toxicity for chironomid larvae at the chosen concentration range (Watts and Pascoe 2000;Milani et al 2003;Vogt et al 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…sediments in the laboratory. The main advantages of chironomids as test species are that they (1) are easy and cheap to culture in the laboratory; (2) spend a large part of their life-cycle as a larva in the sediment; (3) are model organisms for a widespread and species-rich taxonomic order in aquatic ecosystems; (4) are sensitive to pollutants; (5) have a short life-cycle with completing ten or more generations per year under standard conditions and (6) perform sexual reproduction (Benoit et al 1997;Vogt et al 2007a). Furthermore, two guidelines were developed for the routine testing and assessment of chemicals, wherein the larvae were exposed to substances via sediment (OECD 2004a) or via water (OECD 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…The egg-ropes were counted and removed from the breeding container daily. Based on the method described by Vogt et al (2007a), the number of eggs per clutch were recorded. Each egg-mass was placed in a well of a 24-microwell plate and after 3 d the fertility was determined.…”
Section: Methodsmentioning
confidence: 99%
“…Static life-cycle experiments were conducted according to Vogt et al (2007a) at 3 different temperatures. The standard temperature of 20°C was used as the control treatment and 2 treatments with temperature shifts (17 and 23°C) were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Several reported physiological effects on invertebrates, such as Dog-whelks (Nucella lapillus) and sea snails (Thais clavigera) exist at environmental conditions of a few ng/l (Gibbs and Bryan 1986;Horiguchi et al 1997), as well as effects, especially on the immune defence system, of fish and seals (Allner et al 2010;Frouin et al 2008). The effects of organic tin compounds on benthic insects and their larvae, such as chironomids (Diptera: Chironomidae) have been studied less (Nowak et al 2009;Vogt et al 2010;Vogt et al 2007b;Vogt et al 2007a) and should be a target of further research due to their paramount importance as food for, e.g., several fish and bird species (Coffman and Ferrington 1996;Looser et al 2000).…”
Section: Introductionmentioning
confidence: 99%